User Experience Modeling and Simulation for Product Ecosystem Design Based on Fuzzy Reasoning Petri Nets - Feng Zhou; Jiao, R. J.; Qianli Xu; Takahashi, K. (IEEE Transactions on Systems, Man, and Cybernetics - Part A: Systems and Humans, 2012)
Product ecosystem design entails complex user experience (UX) that involves interactions among multiple users, products, and the ambience. This paper aims to capture causal relationships between UX and design elements and in turn to provide decision support to product ecosystem analysis. A fuzzy reasoning Petri net is developed to deal with the uncertainty, complexity, and dynamics associated with UX modeling. Reasoning of diverse constructs of UX is embedded in the fuzzy production rules that are derived from self-report UX data based on rough set mining. A fuzzy reasoning algorithm is implemented to perform parallel inference by multicriteria rules and to simulate most likely UX under different ambient factors. A case study of subway station UX design demonstrates the potential of product ecosystem FRPN formulation.